Introduction to operations research - Hillier, Frederick S.; Lieberman, Gerald J. (McGraw-Hill Education, 2021)
"This book is about Industrial Engineering. The overall thrust of all the revision efforts has been to build upon the strengths of previous editions to more fully meet the needs of today's students. These revisions make the book even more suitable for use in a modern course that reflects contemporary practice in the field"